RELATIONSHIP BETWEEN COGNITIVE FUNCTION AND PHYSICAL ACTIVITY USING NOVEL ACCELEROMETRY DERIVED METRICS. (11th November 2018) - Kuo, P; An, Y; Zipunnukov, V; Urbanek, J; Wanigatunga, A A; Simonsick, E M; Resnick, S; Schrack, J A
Abstract: Given conflicting evidence, the relationship between cognitive function (CF) and physical activity (PA) remains unclear. We investigated the association between standardized cognitive scores for: memory, language, executive functioning, attention, and visuospatial processing, and three accelerometer-based PA metrics: total volume of daily activity on the log scale (TLAC), total daily activity counts (TAC), log total daily activity count (LTAC), and activity fragmentation (AF) among 714 BLSA participants aged > 50 years (49.6% men, age: 71.88 ± 9.99). In multivariable regression models adjusted for age, gender, and years of education, there was no association between executive function and any of the mtrics (p>0.05 for all). Language was associated with all four metrics, memory and visuospatial scores with AF and TLAC, and attention with LTAC, TAC and AF (p<0.05 for all). Results suggest that novel PA metrics capture aspects of PA that may be important for preserving CF. Findings should be confirmed using longitudinal data.